1999
DOI: 10.1021/bi990388e
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Role of Metal Ions in RNA Catalysis:  Kinetic and Thermodynamic Characterization of a Metal Ion Interaction with the 2‘-Moiety of the Guanosine Nucleophile in the Tetrahymena Group I Ribozyme

Abstract: Deciphering the role of individual metal ions in RNA catalysis is a tremendous challenge, as numerous metal ions coat the charged backbone of a folded RNA. Metal ion specificity switch experiments combined with quantitative analysis may provide a powerful tool for probing specific metal ion-RNA interactions and for delineating the role of individual metal ions among the sea of metal ions bound to RNA. We show herein that Mn 2+ rescues the deleterious effect of replacing the 2′-OH of the guanosine nucleophile (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
157
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 66 publications
(180 citation statements)
references
References 44 publications
22
157
1
Order By: Relevance
“…The model in Figure 2 predicts that at low temperature, the interaction of M C with the 2 ' moiety of G will be made even in the absence of bound S+ To test this model, we determined the effect of replacing the Mg 2ϩ ion at site C with Mn 2ϩ on the binding of G N to the free ribozyme and to the E•S complex at 4 8C+ In principle, the specific Mn C 2ϩ •G N interaction needs to be isolated by comparing the effect of replacing Mg C 2ϩ with Mn C 2ϩ on the binding of G N relative to G (Shan & Herschlag, 1999;Shan et al+, 1999a)+ This analysis can be simplified, however, as previous work showed that the binding and reactivity of G and S are the same with Mg 2ϩ or Mn 2ϩ bound at site C (Shan & Herschlag, 1999; data not shown)+ Thus, this aspect of the analysis is not explicitly shown+ Previous work has also established conditions under which Mn 2ϩ replaces Mg 2ϩ at site C, showing that Mn 2ϩ binds 50-fold stronger than Mg 2ϩ , with apparent dissociation constants of 0+28 and 0+21 mM for free E and the E•S complex, respectively, in the presence of 10 mM Mg 2ϩ (30 8C;Shan & Herschlag, 1999;Shan et al+, 1999b)+ 3 Experiments analogous to those carried out at 30 8C showed that at 4 8C, Mn 2ϩ binds to site C in free E and the E•S complex with apparent dissociation constants of 0+28 and 0+20 mM (in 10 mM Mg 2ϩ ), respectively, the same as the Mn C 2ϩ affinity previously observed at 30 8C (data not shown; see footnote 3)+ 4 The Mn C 2ϩ affinity for the E•G N and E•S•G N complexes are stronger than those for free E and the E•S complex; these stronger Mn C 2ϩ affinities presumably arise from the strong interaction of Mn 2ϩ with the 2 ' -amino group of G N in the complexes at 4 8C+ 5…”
Section: Test Of the Two-state Model For Substrate Couplingmentioning
confidence: 99%
See 4 more Smart Citations
“…The model in Figure 2 predicts that at low temperature, the interaction of M C with the 2 ' moiety of G will be made even in the absence of bound S+ To test this model, we determined the effect of replacing the Mg 2ϩ ion at site C with Mn 2ϩ on the binding of G N to the free ribozyme and to the E•S complex at 4 8C+ In principle, the specific Mn C 2ϩ •G N interaction needs to be isolated by comparing the effect of replacing Mg C 2ϩ with Mn C 2ϩ on the binding of G N relative to G (Shan & Herschlag, 1999;Shan et al+, 1999a)+ This analysis can be simplified, however, as previous work showed that the binding and reactivity of G and S are the same with Mg 2ϩ or Mn 2ϩ bound at site C (Shan & Herschlag, 1999; data not shown)+ Thus, this aspect of the analysis is not explicitly shown+ Previous work has also established conditions under which Mn 2ϩ replaces Mg 2ϩ at site C, showing that Mn 2ϩ binds 50-fold stronger than Mg 2ϩ , with apparent dissociation constants of 0+28 and 0+21 mM for free E and the E•S complex, respectively, in the presence of 10 mM Mg 2ϩ (30 8C;Shan & Herschlag, 1999;Shan et al+, 1999b)+ 3 Experiments analogous to those carried out at 30 8C showed that at 4 8C, Mn 2ϩ binds to site C in free E and the E•S complex with apparent dissociation constants of 0+28 and 0+20 mM (in 10 mM Mg 2ϩ ), respectively, the same as the Mn C 2ϩ affinity previously observed at 30 8C (data not shown; see footnote 3)+ 4 The Mn C 2ϩ affinity for the E•G N and E•S•G N complexes are stronger than those for free E and the E•S complex; these stronger Mn C 2ϩ affinities presumably arise from the strong interaction of Mn 2ϩ with the 2 ' -amino group of G N in the complexes at 4 8C+ 5…”
Section: Test Of the Two-state Model For Substrate Couplingmentioning
confidence: 99%
“…To determine whether the metal ion at site C interacts with the 2 ' moiety of G in the E•S•G N complex, the binding of G N to the E•S complex was probed in presteady-state kinetic experiments using the wild-type oligonucleotide substrate, rSA 5 (Table 1), with Mg 2ϩ or Mn 2ϩ bound at site C+ To ensure that the chemical step is rate limiting, the substrate Ϫ1d,rSA 5 (Table 1) was also used; replacement of the 2 ' -OH of U(Ϫ1) with 2 ' -H slows the rate of the chemical step 10 3 -fold, without 3 Ten millimolar Mg 2ϩ was present to ensure proper folding of the ribozyme and to minimize nonspecific binding of Mn 2ϩ to other metal ion sites (Shan & Herschlag, 1999)+ Because a Mg 2ϩ ion is bound at site C at Mg 2ϩ concentrations above 2 mM, the experimentally determined Mn 2ϩ affinities are apparent affinities, representing the exchange of Mn C 2ϩ for Mg C 2ϩ in the presence of 10 mM Mg 2ϩ (Shan & Herschlag, 1999)+ 4 The similar apparent Mn C 2ϩ affinities for E and the E•S complex in the presence of Mg 2ϩ are consistent with the similar Mn 2ϩ and Mg 2ϩ affinities for oxygen ligands (Martell & Smith, 1976;Shan & Herschlag, 1999), such as the nonbridging oxygen of the reactive phosphoryl group of S, as these are ligand exchange reactions with water molecules+ Thus, the presence of S would not be expected to affect the affinity of Mn 2ϩ relative to Mg 2ϩ at site C+ 5 These conclusions are derived from the following observations and analyses+ Replacing Mg C 2ϩ with Mn C 2ϩ increases the G N affinity for free E 20-fold at 4 8C (Table 2)+ Mn C 2ϩ is therefore predicted to bind to the E•G N complex 20-fold stronger than to free E, according to the thermodynamic cycle of equation 2:…”
Section: Test Of the Two-state Model For Substrate Couplingmentioning
confidence: 99%
See 3 more Smart Citations